Influence of microstructure on the mechanical properties and the forming behaviour of very thin metal foils - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (International Journal of Advanced Manufacturing Technology, 2010)
The demand for accurate process design of microforming processes is increasing steadily due to ongoing miniaturisation. Occurring size effects, however, prevent the transfer of existing know-how of standard sheet forming processes with conventional dimensions like blanking, bending and deep drawing on microforming processes. These size effects are either generally valid for all microforming processes, as the influence of the share of surface grains are process-specific, like the influence of large strain gradients as they appear, e.g. in bending processes. A decisive parameter for the occurrence of size effects is the ratio of material mean grain size to foil thickness. For a simulation-based description of microforming processes, the implementation of size-dependent material behaviour in finite element (FE) simulation is essential. Hence, a reliable determination of size-dependent mechanical properties as input data for FE simulation is needed to provide a broad fundamental database for a future theoretical description of microforming processes. In the present paper, the influence of the material microstructure on the mechanical properties of metal foils with thicknesses ranging from 25 to 500 μm is discussed based on tensile tests, bulge tests and fundamental bending experiments. Challenges resulting from the small thickness of the metal foils are pointed out, and future demands regarding determination of material characteristics of thin metal foils are presented. © 2008 Springer-Verlag London Limited.
LFT Import::2019-07-29 (1536)
Keywords: Bending; Hydraulic bulge test; Mechanical properties; Metal foils; Pneumatic bulge test